Як оцінити популяційний вантаж, що пов'язаний з геміклональною гібридизацією в популяційних системах Pelophylax esculentus complex? - Михайлова, О.В.; Усова, О.Є.; Шабанов, Д.А. (Біологія та валеологія., 2011)
How to assess the population load, related with hemiclonal hybridization in Pelophylax esculentus complex population systems? Mykhailova O. V., Usova O. E., Shabanov D. A. – Water frogs, Pelophylax esculentus, are hemiclonal interspecific hybrids. As compared to individuals of parental species their reproduction faces difficulties: gonad development abnormalities, production of aneuploid and unlivable gametes, larval development abnormalities, etc. To date the data, which are necessary to assess the population load of hemiclonality, are fragmentary. It is revealed, that mosaic individuals with aneuploid cells often occur among tadpoles in mixed populations. Diploid hybrid females differ from parental species female (P. ridibundus) with their higher growth rate, but shorter lifetime.
Keywords: Pelophylax esculentus; Сіверсько-Донецький центр різноманіття зелених жаб; гібридизація; геміклональні популяційні системи